USING PROCESS GENRE MODEL TO IMPROVE STUDENTS' WRITING ABILITY - Darakay, Jurney (Pattimura Excellence Journal of Language and Culture, 2025)
This study investigates the implementation of the Process Genre Model (PGM) to improve the narrative writing ability of tenth-grade students (Class X1) at SMA Negeri 11 Ambon. The research employed a classroom action research design conducted in two cycles, each comprising planning, action, observation, and reflection. Students’ writing performance was assessed using a holistic scoring rubric, focusing on content and organization, language use, vocabulary, and mechanics. The results showed significant improvement in students’ narrative writing across the two cycles. In Cycle 1, the majority of students were categorized at the Beginning and Developing levels, while in Cycle 2, 60% of students reached the Expanding level, indicating they had met the indicator of success. The Process Genre Model proved effective in guiding students through a structured writing process while enhancing their understanding of narrative genre conventions. Despite initial challenges, such as confusion in tense use, subject-verb agreement, and mechanical errors, students demonstrated clear progress in content organization, grammar accuracy, and overall writing coherence. The study concludes that the Process Genre Model is a powerful pedagogical tool for improving EFL students’ writing ability and recommends its integration into writing instruction at the secondary level.